Paths to Eurobonds - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2012)
This paper discusses proposals for common euro area sovereign securities. Such instruments can potentially serve two functions: in the short-term, stabilize financial markets and banks and, in the medium-term, help improve the euro area economic governance framework through enhanced fiscal discipline and risk-sharing. Many questions remain on whether financial instruments can ever accomplish such goals without bold institutional and political decisions, and, whether, in the absence of such decisions, they can create new distortions. The proposals discussed are also not necessarily competing substitutes; rather, they can be complements to be sequenced along alternative paths that possibly culminate in a fully-fledged Eurobond. The specific path chosen by policymakers should allow for learning and secure the necessary evolution of institutional infrastructures and political safeguards.